2004
DOI: 10.1002/qua.20165
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite ion formation: Nonempirical simulation in terms of cluster model

Abstract: Neutral and negatively charged nitrogen dioxide molecule either individual or involved in a complex cluster with up to 50 water molecules is nonempirically simulated in the second order of the Møller-Plesset perturbation theory with the unrestricted Hartree-Fock function with the use of atomic basis functions of the 6-31ϩϩG** set and effective fragment potentials for a part of water molecules. The structures corresponding to the local minima of the potential energy surfaces of neutral and anionic clusters are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…There are a small number of ab initio studies of the weakly-bound NO 2 (X ˜2A 1 )-H 2 O complex, either in the gas phase or solvated with additional water molecules. [44][45][46] The global minimum has been found to be a non-hydrogen-bonded C s structure, with the nitrogen of NO 2 closest to the oxygen of water. 45,46 The C s structure of ref.…”
Section: Simulations Of Extended Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a small number of ab initio studies of the weakly-bound NO 2 (X ˜2A 1 )-H 2 O complex, either in the gas phase or solvated with additional water molecules. [44][45][46] The global minimum has been found to be a non-hydrogen-bonded C s structure, with the nitrogen of NO 2 closest to the oxygen of water. 45,46 The C s structure of ref.…”
Section: Simulations Of Extended Systemsmentioning
confidence: 99%
“…[44][45][46] The global minimum has been found to be a non-hydrogen-bonded C s structure, with the nitrogen of NO 2 closest to the oxygen of water. 45,46 The C s structure of ref. 44 which found the oxygens of NO 2 to be closer to the hydrogens of water is likely due to the use of a basis set that was too small.…”
Section: Simulations Of Extended Systemsmentioning
confidence: 99%
“…Kinetic studies have shown that the rate of NO 2 hydrolysis is accelerated in the presence of liquid water films, but the detailed mechanism of the heterogeneous hydrolysis is not clearly understood. Theoretical studies have examined the effect of water solvation on the reaction , and calculated the energetic stability of the water complexes of NO 2 and nitrous acid . These studies indicate that the presence of multiple (up to three) water molecules does not significantly reduce the energy barrier of the hydrolysis compared to nonsolvation.…”
mentioning
confidence: 99%